Quality of service 2.5G for hydrometeorological network in the Chimborazo province, Ecuador - Zúñiga, Byron; Ordóñez, Marco; Ayala, Johanna; Santillán, Daniel; Recalde, Celso (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
This paper describes a model based QoS measurements to quantify the mobile phone network 2.5G in Ecuador currently, since today the quality of service (QoS) in telecommunication is handled in various stages for services: voice, data, streaming This paper is based on 1708 field measurements by means of drive test using machine to machine M2M (AMS-SAMM) between route Riobamba - Cumandá and Riobamba ”“Achupallas - Jubal. the KPI-data (Key Perfomance Indicators) for FTP & HTTP services are estimated through ETSI 102-250 norm and general recommendations ITU-T G.1000; focused service accessibility for evaluate the 2.5G mobile network performance. This QoS model permitted to evaluate access service, service access time, and mean data rate, and verify on nodes accessibility whitin hydrometeorological network in the Chimborazo province, Ecuador, and its results offer an overview Mobile Service. The following results were obtained 91.22 success test percent, 8.78 failed percent, the OP3 present better result for HTTP service and OP2 for FTP service, except at the IP-service Setup Time with 0,14seconds apart in relation to the OP3.